Enhancement of the interfacial polarization resistance of La0.6Sr0.4Co0.2Fe0.8O3-δ cathode by microwave-assisted combustion method. Issue 5 (1st April 2017) - Muhammed Ali, S.A.; Anwar, Mustafa; Somalu, Mahendra Rao; Muchtar, Andanastuti
Abstract: Thermogravimetry, phase formation, microstructural evolution, specific surface area, and electrical properties of La0.6 Sr0.4 Co0.2 Fe0.8 O3−δ (LSCF) cathode were studied as functions of its preparation technique. The pure perovskite LSCF cathode powder was synthesized through glycine–nitrate process (GNP) using microwave heating technique. Compared with conventional heating technique, microwave heating allows the rapid combustion to occur simultaneously between the nitrates and glycine in a controllable manner. The resulting powder is a single-phase nanocrystallite with a mean particle size of 113 nm and a high specific surface area of 12.2 m 2 /g, after calcination at 800 °C. Impedance analysis indicates that microwave heating has significantly reduced the polarization resistance of LSCF cathode. The area specific resistance (ASR) value of 0.059 and 0.097 Ω cm 2 at 800 °C and 750 °C, respectively, were observed. These values were twofold lower than the corresponding ASR of the cathode (0.133 and 0.259 Ω cm 2 at 800 °C and 750 °C, respectively) prepared through conventional heating. Results suggest that the microwave heating GNP strongly contributes to the enhancement of the LSCF cathode performance for intermediate temperature solid oxide fuel cells.